Effect of seed ratio on barnyard millet (Echinochloa frumentacea) - based mixed cropping system - R.V. SlNGH; M.P.S. ARYA (Indian Journal of Agronomy, 2001)
A field experiment on mixed cropping during rainy (kharif) season 1993 and 1994 in barynard millet (Echinochloa frumentacea Link) was conducted under rainfed conditions. The grain yield of barnyard millet was highest (13.06 qlha) in sole crop. It was decreased in all the mixed cropping patterns except barnyard millet + soybean [Glycine max (L.) Merr.] in 90 : 10% seed mixture which recorded the grain yield of 11.78 qiha. Highest land-equivglent ratio (1.45fand barnyard millet equivalent (23.97 q/ha) were also recorded under the same treatment.